Strategi Komunikasi Humas Digital dalam Optimalisasi Engagement Media Sosial Instagram @skaampenan.sdsmp - Ni Luh Gede Mona Agustini; Ida Bagus Benny Surya Adi Pramana; Rieka Yulita Widaswara (MUKASI: Jurnal Ilmu Komunikasi, 2026)
This study aims to examine the role of the Digital PR communication strategy in optimizing Instagram social media engagement @skaampenan.sdsmp. Currently, social media has become a primary channel for disseminating information to the public quickly and interactively. This research employs an in-depth qualitative approach, collecting data through interviews, observations, and documentation. The results indicate that the PR division of SKA Ampenan plays a crucial role in designing, managing, and evaluating content to ensure that messages are conveyed effectively, relevantly, and engagingly to the audience. Instagram is utilized to share news about school activities, build a positive institutional image, and reach a wider audience through features such as posts, short videos, and stories. Audience engagement, such as likes, comments, and shares, serves as an indicator of the effectiveness of information dissemination. The study also identifies several challenges faced by the PR division, including Instagram algorithm changes, limited staff capacity, diverse audience preferences, and low public participation in providing feedback. In conclusion, a well-planned and consistent digital communication strategy is essential. The PR division of SKA Ampenan successfully enhances the effectiveness of information dissemination and fosters a positive school image. Recommendations include improving human resource competencies, developing interactive content, and adjusting digital communication strategies according to audience characteristics.